Oil Wells. Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
This vintage picture showcases an oil field with several oil derricks erected in the background, a long shed with a galvanize roof at mid-ground and several stacks on the right horizon, with smoke emerging from one of them. A vintage car is parked on the access road in the foreground.
Colour: Black and White; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Petroleum industry and trade--Trinidad and Tobago; Cranes, derricks, etc.--Trinidad and Tobago; Sheds--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Rural roads--Trinidad and Tobago; Oil fields--Trinidad and Tobago; [1910]